Access to healthcare among Chinese immigrants living in Seville, Spain - Bárbara Badanta-Romero; Giancarlo Lucchetti; Sergio Barrientos-Trigo (Elsevier, 2021)
Objective: To investigate the use of healthcare services and factors associated with accessing them among Chinese immigrants living in Southern Spain. Method: A mixed methodology was used. A cross-sectional survey was first administered to Chinese immigrants (n = 133), and they were asked about their visits to the doctor, use of emergency services, and hospitalization. A phenomenological approach was then used with key informants (n = 7). In the interviews, additional information, such as barriers and facilitators to improving accessibility, was explored. Results: In the previous year, 51% had visited a doctor and 34% had visited an Emergency Department. The main reasons for hospitalization were pregnancy (37.5%) and surgery (25%). At least 20% of the sample reported having never visited a doctor. Language difficulties and time constraints were identified as important barriers to accessibility. Sex differences were found among the reasons for lack of time, which, in men, were related to work (odds ratio [OR] = 7.7) and, in women, were related to childcare (OR = 12). The majority of Chinese immigrants preferred to use Traditional Chinese Medicine as their first treatment rather than visiting a doctor. Conclusions: A lower use of health services was found among Chinese immigrants in Spain compared to the native population. When using health services, they choose acute care settings. Communication and waiting times are highlighted as major barriers. Adapting these demands to the healthcare system may help immigrants to trust their healthcare providers, thus increasing their use of health services and improving their treatment. Resumen: Objetivo: Investigar el uso y los factores asociados al acceso a los servicios de salud en inmigrantes chinos residentes en el sur de España. Método: Se utilizó una metodología mixta. Primero se administró una encuesta transversal a inmigrantes chinos (n = 133). Se les preguntó sobre sus visitas al médico y el uso de servicios de emergencia y de hospitalización. Luego se utilizó un enfoque fenomenológico con informantes clave (n = 7), explorando información adicional, como barreras y facilitadores para mejorar la accesibilidad. Resultados: El último año, el 51% había visitado al médico y el 34% un servicio de urgencias. La hospitalización se debió principalmente a embarazo (37,5%) y cirugía (25%). El 20% informó que nunca había visitado al médico. Las dificultades de lenguaje y las limitaciones de tiempo fueron barreras importantes para la accesibilidad. Se encontraron diferencias de sexo para la falta de tiempo; en hombres se relacionaron con el trabajo (odds ratio [OR] = 7,7) y en mujeres con el cuidado infantil (OR = 12). La mayoría prefirió usar medicina tradicional china como primer tratamiento en lugar de visitar al médico. Conclusiones: Se encontró un menor uso de los servicios de salud entre los inmigrantes chinos en España en comparación con la población autóctona. Al utilizar los servicios de salud, eligen los cuidados agudos. La comunicación y los tiempos de espera destacan como barreras principales. Adaptar estas demandas al sistema de salud puede ayudarles a confiar en sus proveedores de atención médica, aumentando el uso de los servicios de salud y mejorando su tratamiento.